P12—Fabry Disease in Latin America: A Report From the Fabry Registry (2012)
Fabry disease is a rare lysosomal storage disorder caused by a deficient activity of the lysosomal enzyme ?-galactosidase A. The Fabry Registry is a global, observational, and voluntary program designed to collect clinical data related to the onset, progression, and treatment of Fabry disease.